2009
DOI: 10.1021/ma8023377
|View full text |Cite
|
Sign up to set email alerts
|

Reversible, Nondegradative Conversion of Crystalline Aromatic Poly(ether ketone)s into Organo-Soluble Poly(ether dithioketal)s

Abstract: Crystalline aromatic poly(ether ketone)s such as PEEK and PEK may be cleanly and reversibly derivatized by dithioketalization of the carbonyl groups with 1,2-ethanedithiol or 1,3-propanedithiol under strong acid conditions. The resulting 1,3-dithiolane and 1,3-dithiane polymers are hydrolytically stable, amorphous, and readily soluble in organic solvents such as chloroform and THF and are thus (unlike their parent polymers) easily characterized by gel permeation chromatography (GPC). GPC analysis of a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 35 publications
(49 reference statements)
0
48
0
Order By: Relevance
“…Turner and colleagues and Colquhoun et al . had previously reported studies on the structure and molecular weight respectively of insoluble polyetheretherketone (PEEK) by MALDI‐TOF, wherein soluble PEEK oligomers or soluble modified PEEK derivative‐like poly(ether dithioketal) were used as the model . However, the appropriate models of 10a have not been found so far for structure analysis because the MALDI‐TOF technique favors the ionization of soluble low molecular weight species .…”
Section: Resultsmentioning
confidence: 99%
“…Turner and colleagues and Colquhoun et al . had previously reported studies on the structure and molecular weight respectively of insoluble polyetheretherketone (PEEK) by MALDI‐TOF, wherein soluble PEEK oligomers or soluble modified PEEK derivative‐like poly(ether dithioketal) were used as the model . However, the appropriate models of 10a have not been found so far for structure analysis because the MALDI‐TOF technique favors the ionization of soluble low molecular weight species .…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary studies showed that prolonged reactions (18)(19)(20) Analysis of poly(ether ketal)s by 1 H NMR spectroscopy showed no detectable dithioketal residues, but deprotected ketonic units were present at levels of between 5 and 45 mole%. Both PEEK-1,3-dithiolane (1) and PEEK-1,3-dithiane (2) successfully participated in this reaction, forming the same end-products.…”
Section: Reactions Of Peek Dithioketals With Ethane-12-diolmentioning
confidence: 99%
“…9-14 Amongst the first efforts was that of Kelsey et al, 14 With specific relevance to the present work, a further novel approach to fully-reversible derivatisation of poly(arylene ether ketone)s has been reported. 18,19,20 The carbonyl groups were protected by reaction with dithiols such as 1, The dithioketalization approach offers a general, non-degradative pathway for reversible chemical modification of any poly(arylene ether ketone). However, removal of the dithioketal group is generally slow and difficult (though achievable), 19 chemistry, cyclic dithioketals are also difficult to hydrolyze but they do participate in exchange reactions, for example with ethane-1,2-diol or 2-mercaptoethanol in the presence of a catalyst such as mercury(II) chloride, yielding the corresponding 1,3-dioxolanes or 1,3-oxathiolanes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the molecular weights and polydispersities, the copolymers were first transformed into dithioketals following Colquhoun et al (24). This reaction results in soluble polyetherketone, but unfortunately, in the case of the copolymers, solubility was much lower, too low for size exclusion chromatography to yield any data.…”
Section: Polymer Synthesismentioning
confidence: 99%